2015
DOI: 10.1002/dep2.2
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological and sedimentological processes of flood layer formation in Lake Mondsee

Abstract: Detrital layers in lake sediments are recorders of extreme flood events. However, their use for establishing time series of past floods is limited by lack in understanding processes of detrital layer formation. Therefore, we monitored hydro-sedimentary dynamics in Lake Mondsee (Upper Austria) and its main tributary, Griesler Ache, over a 3-year period from January 2011 to December 2013. Precipitation, discharge and turbidity were recorded continuously at the river outlet to the lake and compared to sediment fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…18,000e19,000 cal years BP (Reitner, 2007;van Husen, 1977van Husen, , 1997. The lake is at present mainly monomictic with a long stratification period between late April and December and mixing during winter/early spring; dimictic conditions with a short winter stagnation of a few weeks occur only sporadically during the rare years with ice cover (Dokulil and Skolaut, 1986;Ficker et al, 2017;K€ ampf et al, 2015). Mondsee is fed by three major tributaries (Fuschler Ache, Zeller Ache, Wangauer Ache), which account for~70% of the total inflow, as well as several minor creeks.…”
Section: Introductionmentioning
confidence: 99%
“…18,000e19,000 cal years BP (Reitner, 2007;van Husen, 1977van Husen, , 1997. The lake is at present mainly monomictic with a long stratification period between late April and December and mixing during winter/early spring; dimictic conditions with a short winter stagnation of a few weeks occur only sporadically during the rare years with ice cover (Dokulil and Skolaut, 1986;Ficker et al, 2017;K€ ampf et al, 2015). Mondsee is fed by three major tributaries (Fuschler Ache, Zeller Ache, Wangauer Ache), which account for~70% of the total inflow, as well as several minor creeks.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent studies provide evidence that the deposition of sediment in lakes is sensitive to numerous internal and external forcing mechanisms that are often difficult to differentiate from the analysis of sediments. For example, it was demonstrated that flood deposits are not consistently related to the highest rainfall event, as frequently inferred [ Kämpf et al ., ]. Hence, understanding sedimentary processes within lakes is critical in assessing the hydroclimate record of sediments.…”
Section: Introductionmentioning
confidence: 99%
“…The sediments were monitored with two moored sediment traps ( Fig. 1) at a 3 d time resolution from January 2011 to November 2013 (proximal trap) and from April 2012 to November 2013 (distal trap) (for details, see Kämpf et al, 2015). Stable oxygen and carbon values were determined for all samples.…”
Section: Study Site and Methodsmentioning
confidence: 99%
“…Here, we present stable oxygen and carbon isotope compositions of carbonates from sediment cores, sediment traps, and the catchment to discuss their potential for reconstructing both flood frequencies and magnitudes. We have selected Lake Mondsee (in the Upper Austrian region of the Salzkammergut) because the sediments are annually laminated and contain both endogenic calcite and flood-triggered detrital carbonates (Lauterbach et al 2011;Swierczynski et al, 2012;Kämpf et al, 2014Kämpf et al, , 2015. The sediment composition resembles that of other alpine lake sediments (Filippi et al, 1998;Czymzik et al, 2010;Wirth et al, 2013), suggesting that the Lake Mondsee sediment record could be representative for other alpine lakes as well.…”
Section: Introductionmentioning
confidence: 99%